RANCANG BANGUN SISTEM INFORMASI DAFTAR ULANG PENERIMAAN PESERTA DIDIK BARU PADA SMK NEGERI 12 SAMARINDA BERBASIS WEBSITE - Sumardi (JAMINFOKOM - Jurnal Manajemen Informatika dan Komputer, 2022)
In helping the school's re-registration in reducing the errors of data collection of new students the need to create a new student registration information system, then a new student registration information system was created at SMKN 12 Samarinda-based website. The system development method used in this thesis is the waterfall method, while the tools used in the development of the thesis system are FOD, CD, DFD, Data Dictionary, ERD and HIPO, and making systems using the PHP Programming language and MySQL database management system. Beta testing results show that 81% of respondents said that this system meets 6 good website criteria. 100% of respondents (Administrative) said that this system helped the work of administration. Suggestions from the thesis of the new student re-registration information system is the addition of the autofill feature to the form on the system to re-register classes 11 and 12 by logging in, as well as adding other features to complete and facilitate administration, prospective new students and the re-registration committee.